Serum vitamin E and cardiovascular diseases risk: a J-shaped association in a large cross-sectional study - Jian Li; Changqing Li; Lin Tao; Lei Wang; Gang Wang; Youqi Kong; Lichun Zhou (BMC Cardiovascular Disorders)
Abstract Objective Cardiovascular diseases (CVDs) has been identified as a primary cause of mortality on a global scale. The present study was conducted with the objective of investigating the association between serum vitamin E levels and the risk of developing CVDs, with the aim of identifying potential risk thresholds. Methods Using National Health and Nutrition Examination Survey (NHANES) data from 1999 to 2002, we included 3,516 adult participants. Serum vitamin E concentrations were measured by high-performance liquid chromatography, and CVDs status was assessed through medical questionnaires and interviews. Multivariable logistic regression and segmented linear models analyzed the association between serum vitamin E and CVDs risk. Results A J-shaped relationship between serum vitamin E and CVDs risk was observed. Segmented linear regression revealed a nonlinear association between vitamin E concentration and CVDs incidence. At low concentrations (below 85.24 µg/dL), although the OR suggested a potential protective trend (OR: 0.968, 95% CI: 0.926–1.011), this association did not reach statistical significance (P = 0.1422), indicating no conclusive evidence of risk reduction. Beyond this threshold, CVDs risk significantly increased (OR: 1.056, 95% CI: 1.003–1.112, P = 0.0377). Notably, the high-concentration group demonstrated a substantially elevated CVDs risk, with a 4.18-fold increase (OR: 4.18, 95% CI: 2.84–6.16, P < 0.0001). Conclusion Maintaining serum vitamin E levels within an optimal range is crucial for reducing CVDs risk. The study reveals the complex nonlinear relationship between vitamin E concentration and disease risk, providing important insights for clinical practice and public health strategies.